Globalisation and enlargement of the European union : Austrian and Swedish social forces in the struggle over membership - Bieler, Andreas, 1967- (London ; New York : Routledge, 2000)
On January 1 1995, Austria and Sweden joined the European Union (EU). This book examines why these two countries joined at such a moment and studies their accession against the structural background of globalization. In this cutting-edge analysis, Andreas Bieler argues that conventional neo-functionalist and intergovernmentalist theories fail to explain such structural change as they take existing power structures as given. Therefore, he develops a neo-Gramscian perspective as an alternative approach to European integration.
Chapter 1 Introduction: theories of integration and Austria's and Sweden's accession to the European Union-- a critique and alternative -- Theories of integration and Austria's and Sweden's accession to the European Union--a critique and alternative -- chapter 2 Austria and Sweden in an era of global structural change -- chapter 3 Social forces and the struggle for application in Austria and Sweden -- chapter 4 The conflict over the EU referenda in Austria and Sweden From the EEA via Maastricht and membership negotiations -- chapter 5 Austria's and Sweden's accession to the EU and the changing security structure -- chapter 6 The future enlargement of the EU towards Central and Eastern Europe -- chapter 7 Conclusions: globalisation, EU enlargement and the limits of neo-liberalism A neo-Gramscian perspective as an alternative -- Globalisation, EU enlargement and the limits of neo-liberalism.
Includes bibliographical references (pages 169-191) and index.
Print version record.
eBooks on EBSCOhost
Keywords: European Union -- Austria; European Union -- Sweden; Austria -- Economic conditions -- 1945-; Sweden -- Economic conditions -- 1945-; Autriche -- Conditions économiques -- 1945-; Suède -- Conditions économiques -- 1945-; BUSINESS & ECONOMICS -- International -- General; BUSINESS & ECONOMICS -- International -- Economics; Economic history; Austria; Sweden; Since 1945